2022
DOI: 10.1093/jnen/nlac056
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Brain Regional Detection, Histopathology, Gene Expression, and Immunomodulatory Changes in Decedents with COVID-19

Abstract: Brains of 42 COVID-19 decedents and 107 non-COVID-19 controls were studied. RT-PCR screening of 16 regions from 20 COVID-19 autopsies found SARS-CoV-2 E gene viral sequences in 7 regions (2.5% of 320 samples), concentrated in 4/20 subjects (20%). Additional screening of olfactory bulb (OB), amygdala (AMY) and entorhinal area for E, N1, N2, RNA-dependent RNA polymerase, and S gene sequences detected one or more of these in OB in 8/21 subjects (38%). It is uncertain whether these RNA sequences represent viable v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 255 publications
(198 reference statements)
0
34
0
Order By: Relevance
“…Perivascular cuffing (Fig. 3b) is well described in histological examinations of brains from deceased COVID-19 patients 38,39,56,87,88 . Other lesions observed in the BA.5-infected K18-hACE2 mouse brains, that have also been described in post-mortem COVID-19 patients, include perivascular edema (Fig.…”
Section: Lesions In the Brains Of Ba5 Infected K18-hace2 Mice Identif...mentioning
confidence: 67%
See 2 more Smart Citations
“…Perivascular cuffing (Fig. 3b) is well described in histological examinations of brains from deceased COVID-19 patients 38,39,56,87,88 . Other lesions observed in the BA.5-infected K18-hACE2 mouse brains, that have also been described in post-mortem COVID-19 patients, include perivascular edema (Fig.…”
Section: Lesions In the Brains Of Ba5 Infected K18-hace2 Mice Identif...mentioning
confidence: 67%
“…Infection of K18-hACE2 mice with original ancestral isolates via intranasal inoculation, usually results in fulminant and lethal brain infections, with virus likely entering the brain via the olfactory epithelium, across the cribriform plate and into the olfactory bulb [49][50][51][52][53][54] . This route of entry into the brain may also be relevant for COVID-19 patients 35,38,39,[55][56][57] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong anterior emphasis of these effects may be traced back to the role of the olfactory bulb (OB) as the most likely entry point for SARS-CoV-2 in the brain (Serrano et al, 2022; Xydakis et al, 2021). The OB has been shown to be the most likely brain region to contain SARS-CoV-2 and shows significant changes in gene expression in COVID-19 (Serrano et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The strong anterior emphasis of these effects may be traced back to the role of the olfactory bulb (OB) as the most likely entry point for SARS-CoV-2 in the brain (Serrano et al, 2022; Xydakis et al, 2021). The OB has been shown to be the most likely brain region to contain SARS-CoV-2 and shows significant changes in gene expression in COVID-19 (Serrano et al, 2022). Moreover, studies examining the brain vasculature in deceased COVID-19 patients showed strong fibrinogen staining in the OB, indicating a leaky blood-brain barrier (BBB) at autopsy (Lee et al, 2022).…”
Section: Discussionmentioning
confidence: 99%